Platinum-based chemotherapy for pancreatic cancer: impact of mutations in the homologous recombination repair and Fanconi anemia genes. (March 2022) - Emelyanova, Marina; Pudova, Elena; Khomich, Darya; Krasnov, George; Popova, Anna; Abramov, Ivan; Mikhailovich, Vladimir; Filipenko, Maxim; Menshikova, Sofia; Tjulandin, Sergey; Pokataev, Ilya
Background: Mutations in homologous recombination (HR) and Fanconi anemia (FA) genes may predispose to pancreatic cancer (PC) and enable the prediction of sensitivity to platinum-based chemotherapy. FOLFIRINOX is a standard treatment option for non-selected PC patients and could be effective due to undiagnosed DNA repair deficiency. Here, we aimed to determine the frequency of mutations in genes involved in the HR and FA pathways, evaluate their clinical implications, and determine the objective response rate (ORR), progression-free survival (PFS), and overall survival (OS) of PC patients treated with platinum. Methods: We performed targeted DNA sequencing of 30 genes ( ABRAXAS1, ATM, ATR, BARD1, BLM, BRCA1, BRCA2, BRIP1, CDKN2A, CHEK1, CHEK2, FANCC, FANCF, FANCG, FANCI, FANCL, FANCM, MRE11A, NBN, PALB2, PTEN, RAD50, RAD51C, RAD51D, RAD52, RAD54B, RBBP8, RINT1, SLX4, and XRCC2 ) for 543 PC patients. Results: In BRCA/PALB2 -mutated patients with advanced PC (33 patients, 6.1%), the PFS and OS were higher for first-line platinum therapy than for non-platinum therapy [PFS: HR = 0.28, 95% confidence interval (CI) = 0.10–0.81, p = 0.02; OS: HR = 0.31, 95% CI = 0.08–1.16, p = 0.08]. Among 93 patients (17.1%) with mutations in other HR/FA genes, no statistically significant difference in PFS and OS was observed between first-line platinum therapy and non-platinum therapy (PFS: HR = 0.83, 95% CI = 0.43–1.62, p = 0.59; OS: HR = 0.58, 95% CI = 0.28–1.22, p = 0.15). For patients with early PC, no prognostic value was observed for BRCA1/2, PALB2, or other HR/FA genes mutations. Moreover, a personal history of breast, ovarian, pancreatic, or prostate cancer was identified as the only independent predictor of the risk of BRCA/PALB2 mutations (HR = 5.83, 95% CI = 2.16–15.73, p < 0.01). Conclusion: Mutations in the BRCA1/2 and PALB2 genes increase the sensitivity of PC to platinum agents. Thus, alterations in these genes in PC patients must be determined prior to anticancer therapy.